Childhood/adolescent smoking and adult smoking and cessation: The International Childhood Cardiovascular Cohort (i3C) Consortium - Hu, T; Gall, SL; Widome, R; Bazzano, LA; Burns, TL; Daniels, SR; Dwyer, T; Ikonen, J; Juonala, M; Kähönen, M; Prineas, RJ; Raitakari, O; et al. (Wiley, 2020)
Background: Despite declining US adolescent smoking prevalence from 40% among 12th graders in 1995 to around 10% in 2018, adolescent smoking is still a significant problem. Using the International Childhood Cardiovascular Cohort (i3C) Consortium, which includes 7 international cohorts recruited in childhood and followed into adulthood, the present study was designed to confirm the important relation between adolescent smoking and daily adult smoking and present new data on adult smoking into the forties and comparison of smoking in the United States, Finland, and Australia.